2023
DOI: 10.1136/ard-2023-224990
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of genetic testing and targeted intervention to prevent the development and progression of Paget’s disease of bone

Jonathan Phillips,
Deepak Subedi,
Steff C Lewis
et al.

Abstract: IntroductionPaget’s disease of bone (PDB) frequently presents at an advanced stage with irreversible skeletal damage. Clinical outcomes might be improved by earlier diagnosis and prophylactic treatment.MethodsWe randomised 222 individuals at increased risk of PDB because of pathogenicSQSTM1variants to receive 5 mg zoledronic acid (ZA) or placebo. The primary outcome was new bone lesions assessed by radionuclide bone scan. Secondary outcomes included change in existing lesions, biochemical markers of bone turno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Indeed, in a recent screening of baseline clinical, radiological and bone scan characteristics of 222 apparently unaffected carriers of SQSTM1 mutations (from known PDB families) who took part in the Zoledronic acid in the Prevention of Paget’s disease (ZiPP) study, asymptomatic PDB was confirmed in about 9% of cases [ 52 ]. Importantly, in the very recent report of that trial, after a median duration of 84 months, zoledronate-treated subjects did not develop any new pagetic lesion compared to placebo [ 68 ]. An improvement of existing lesions (completely disappearing on bone scan in 87% of cases) was also demonstrated in zoledronate-treated subjects versus placebo.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Indeed, in a recent screening of baseline clinical, radiological and bone scan characteristics of 222 apparently unaffected carriers of SQSTM1 mutations (from known PDB families) who took part in the Zoledronic acid in the Prevention of Paget’s disease (ZiPP) study, asymptomatic PDB was confirmed in about 9% of cases [ 52 ]. Importantly, in the very recent report of that trial, after a median duration of 84 months, zoledronate-treated subjects did not develop any new pagetic lesion compared to placebo [ 68 ]. An improvement of existing lesions (completely disappearing on bone scan in 87% of cases) was also demonstrated in zoledronate-treated subjects versus placebo.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…In Lancaster in the north-west of England the prevalence of PDB has fallen by an order of magnitude—from 8 to 0.8%—in 40 years [ 21 ]. In the ZiPP study of SQSTM1 mutation carriers, the rate at which PDB had developed in the placebo group by the end of the study (2021) was only one eighth that anticipated when the study was registered 13 years earlier [ 22 ]. So there is little question that the nature of Paget’s disease has changed from its apparent peak in the late nineteenth and early twentieth century.…”
Section: The Changing Epidemiologymentioning
confidence: 99%